CITRA PEREMPUAN DALAM NASKAH SYAIR NABI ALLAH AYUB (ANONYMOUS) DALAM PRESPEKTIF ISLAM: KAJIAN SEMIOTIK - Idayanti, Iik; Sudiar, Nining; Yuhelmi, Yuhelmi (Jurnal Ilmu Budaya, 2017)
A manuscript entitled Syair Nabi Allah Ayub becomes the object of this study. It is written in Jawi. The manuscript was fisnished in the Barus, on 24-3-1273 or 22-11-1856. The text contains the life journey of the Prophet Ayub being tested by God with various trials. At the end of story, Angel Jibril and Mikail released all the trials and the Prophet Ayub regained its former glory. Many things can be explored with regard to the content of the texts, one of them about the imagery of woman in Islam described in the text of Syair Nabi Allah Ayub. It is analyzed by using Roland Barthes’ semiotic concept.